Concept Understanding, Environmental Care Character, and Student Responses in Elementary School Thematic Subjects - Supian Ramli; Ramazani Novanda; Muhammad Sobri (Jurnal Ilmiah Sekolah Dasar, 2022)
Students' understanding and the character of students' environmental care still need to be developed. This study aims to analyze the differences and relationships of the variables of concept understanding, environmental care character, and student responses in elementary schools on thematic subjects. This study uses mixed research methods designed with an explanatory design. Explanatory design is carried out in several stages of research, first by collecting data, second by analyzing the data and third by formulating the results of the analysis quantitatively, then proceeding with data collection, analyzing and formulating qualitative data, and ending with interpreting the research results. Data collection in this study used instruments in the form of observation sheets and questionnaires. Data analysis was carried out qualitatively and quantitatively. The results of the t-test and correlation test on the variables of conceptual understanding, environmental character, and student responses in elementary schools on thematic subjects can be said to be good but need to be improved optimally so that these variables are beneficial for students. The conclusion of this study is that there is a comparison of concept understanding, environmental care character, and response in two elementary schools on thematic subjects and there is a relationship between concept understanding, environmental care character, and student responses in two elementary schools on thematic subjects.